Epistemic Agency in Multimodal Reading: How Primary Learners Construct Knowledge Across Modes - Hasna Fitri Labibah; Januarius Mujiyanto; Dwi Rukmini; Widhiyanto Widhiyanto (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractReading literacy remains a persistent challenge in many English as a Foreign Language (EFL) contexts. However, primary EFL learners frequently encounter difficulties in integrating linguistic, visual, spatial, and gestural modalities. This study investigates how primary learners exercise epistemic agency in multimodal reading and construct knowledge across different modes. Utilizing multimodality theory and epistemic agency, the study implemented an explanatory sequential mixed-methods design involving thirty fifth-grade students from Madrasah Ibtidaiyah Negeri (MIN) 1 Tulang Bawang Barat, Lampung. In Phase 1, a one-group pretest–posttest design measured changes in multimodal comprehension using a validated twenty-item instrument. Results showed significant improvement, with mean scores rising from 61.40 (SD = 8.25) to 74.30 (SD = 7.80), t(29) = 8.52, p < 0.001, and Cohen’s d = 1.56, indicating a large effect. In Phase 2, six students representing varied improvement levels were interviewed and engaged in task-based reflections. Thematic analysis identified five dimensions of epistemic agency: taking initiative, decision-making across modes, justification of understanding, reflection and self-regulation, and collaboration and dialogue. The integration of both phases demonstrated that learners' agentive engagement with multimodal resources underpinned comprehension gains, transforming affordances into strategies for meaning-making. These findings affirm that multimodal pedagogy fosters not only measurable comprehension outcomes but also autonomy, critical thinking, and collaborative engagement. The study recommends embedding multimodal literacy into EFL curricula and providing scaffolds that balance cognitive support with opportunities for agency.Keywords: epistemic agency, knowledge construction, literacy pedagogy, multimodal reading, primary school. AbstrakLiterasi membaca tetap menjadi tantangan yang terus-menerus dalam banyak konteks Bahasa Inggris sebagai Bahasa Asing (EFL). Namun, pembelajar EFL tingkat dasar sering menghadapi kesulitan dalam mengintegrasikan modalitas linguistik, visual, spasial, dan gestural. Studi ini menyelidiki bagaimana pembelajar primer menjalankan agensi epistemik dalam membaca multimodal dan membangun pengetahuan di berbagai moda. Dengan memanfaatkan teori multimodalitas dan agensi epistemik, penelitian ini menerapkan desain metode campuran sekuensial eksplanatif yang melibatkan tiga puluh siswa kelas lima dari Madrasah Ibtidaiyah Negeri (MIN) 1 Tulang Bawang Barat, Lampung. Pada Fase 1, desain pretes-postes satu kelompok mengukur perubahan dalam pemahaman multimodal menggunakan instrumen dua puluh item yang tervalidasi. Hasil menunjukkan peningkatan yang signifikan, dengan skor rata-rata meningkat dari 61,40 (SD = 8,25) menjadi 74,30 (SD = 7,80), t(29) = 8,52, p < 0,001, dan Cohen's d = 1,56, yang menunjukkan efek yang besar. Pada Fase 2, enam siswa yang mewakili berbagai tingkat peningkatan diwawancarai dan dilibatkan dalam refleksi berbasis tugas. Analisis tematik mengidentifikasi lima dimensi agensi epistemik: mengambil inisiatif, pengambilan keputusan lintas moda, pembenaran pemahaman, refleksi dan pengaturan diri, serta kolaborasi dan dialog. Integrasi kedua fase menunjukkan bahwa keterlibatan agen pembelajar dengan sumber daya multimoda mendukung perolehan pemahaman, mengubah affordance menjadi strategi untuk pembuatan makna. Temuan ini menegaskan bahwa pedagogi multimoda tidak hanya mendorong hasil pemahaman yang terukur tetapi juga otonomi, pemikiran kritis, dan keterlibatan kolaboratif. Studi ini merekomendasikan penanaman literasi multimodal ke dalam kurikulum EFL dan menyediakan perancah yang menyeimbangkan dukungan kognitif dengan peluang untuk agensi.Kata kunci: agensi epistemik, konstruksi pengetahuan, pedagogi literasi, membaca multimodal, sekolah dasar.